2011
DOI: 10.4103/2229-5070.72107
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis of cystic echinocooccosis by antigen detection in serum, urine, and saliva samples

Abstract: Background:Cystic echinococcosis (CE) being more common in rural areas, the collection of serum may not always be possible or may be hazardous in untrained hands. The alternative, noninvasive samples like saliva and urine which are non invasive and easy to collect need to be evaluated for diagnosis of CE.Aim:The aim of this study was to evaluate hydatid antigen detection by ELISA in urine and saliva samples by comparing them with antigen detection in serum for diagnosis of CE.Materials and Methods:Serum, saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the current study, ELISA and IHA were used to diagnose CE in a sub-set of patients (n = 48). However, the usefulness of serology is limited due to poor sensitivity and the possibility of cross-reactions occurring with other parasitic infections (Chaya and Parija 2013;Dubey et al 2011;Schantz et al 1980;Swarna and Parija 2012;Wuestenberg et al 2014). Because of these reasons, patients are typically not diagnosed based on serology alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ELISA and IHA were used to diagnose CE in a sub-set of patients (n = 48). However, the usefulness of serology is limited due to poor sensitivity and the possibility of cross-reactions occurring with other parasitic infections (Chaya and Parija 2013;Dubey et al 2011;Schantz et al 1980;Swarna and Parija 2012;Wuestenberg et al 2014). Because of these reasons, patients are typically not diagnosed based on serology alone.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of LAMP with LFD was used to identify hepatopancreatic parvovirus in prawns. The study showed that the LAMP-LFD method is a remarkably sensitive, secure, and expeditious technique [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The type and purity of the antigen used influence the effectiveness of immunodiagnostic testing for cystic echinococcosis [ 25 ]. The presence of antigen–antibody immune complexes can also reduce the sensitivity of antigen detection tests for cystic echinococcosis [ 24 ]. A LAMP technique was devised to identify E. granulosus with a sensitivity of 100 fg per 200 μL of distilled water [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been seen that up to 40% of peroperatively confirmed cases of hydatid cyst may be negative for hydatid specific antibodies. [57] Detection of circulating hydatid antigen in the serum has been evaluated to be useful in the diagnosis of active infection as these antigen levels decrease after chemotherapy or surgical resection of the hydatid cysts. ELISA, countercurrent immunoelectrophoresis (CIEP), reverse passive haemagglutination (RPHA) and latex agglutination have all been evaluated for hydatid antigen detection in serum and other samples.…”
Section: Antigen Detectionmentioning
confidence: 99%